Method and apparatus for coating bone particles using messes
The application of nanocoating through multiple stacked mesh structures solves the problem of difficulty in applying bone particles, improves the biological activity of bone particles and bone remodeling effect, and achieves a more uniform and efficient coating formation.
Patent Information
- Application Number
- CN202380045241.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-05-25
- Publication Date
- 2025-01-14
AI Technical Summary
Existing bone repair materials have difficulty applying nanocoating efficiently, resulting in poor biological activity and bone remodeling of bone particles, and difficulty in controlling coating size and surface area.
Using multiple stacking mesh methods, smaller bone particles and coating fluid are allowed to pass through through openings of different sizes, while larger bone particles remain on the mesh, using the mesh structure to make the bone particles come into contact with the coating fluid, Increase the coating surface area and control the coating thickness.
Improves the biological activity of bone particles, enhances bone remodeling capabilities, simplifies the coating application process, reduces manual operation, and improves the uniformity and quality of the coating.
Smart Images

Figure CN119317455A_ABST
Abstract
Description
Background Art
[0001] Bone defects or bone voids may be caused by a variety of different factors, including but not limited to trauma, pathological diseases or surgical interventions. Since bones can provide both stability and protection for the organism, these defects or voids may cause problems. In order to address these defects or voids, compositions comprising natural and synthetic materials have been developed. Bone particles, whether natural bone (e.g., allogeneic bone) or synthetic bone (e.g., ceramic, polymer), can be used to grow bone in bone defects. Bone particles can be used to repair bone and impart the biological and / or mechanical properties required for bone defects depending on the materials contained in them.
[0002] A variety of bone repair materials and bone void materials are used in the medical field. Autologous cancellous bone is one type of bone void filler that is used. This type of bone has the advantages of being osteoinductive and non-immunogenic. Unfortunately, this type of bone is not often available. In addition, morbidity and trauma to the donor site add to the limitations of autologous cancellous bone.
[0003] Allogeneic bone is a logical bone graft alternative to autologous bone. It is easily obtained from cadavers, avoiding the surgical complications and patient morbidity associated with harvesting autologous bone. Allogeneic bone is essentially a load-bearing matrix containing cross-linked collagen, hydroxyapatite, and osteoinductive bone morphogenetic proteins (BMPs). Human allogeneic bone is widely used in orthopedic surgery. However, allogeneic bone does not always have the same strength properties or cells and proteins that can influence new bone growth as provided by autologous bone graft. In addition, when allogeneic bone is used, there is a small chance of disease transmission and reduced effectiveness due to the removal of bone growth cells and proteins during the cleaning and sterilization process.
[0004] Alternatives to autologous and allogeneic bone are synthetic bone materials, such as ceramic-based bone materials. Hybrid materials consisting of organic polymers coated with inorganic minerals have attracted much attention in medicine due to their combination of favorable properties. Polymeric materials are desirable matrix materials for biomedical applications because they can be processed into a variety of sizes and geometries and can be designed to bioresorb or bioabsorb in a controllable time frame. Therefore, polymeric biomaterials are characterized by a variety of applications, including medical devices, tissue engineering scaffolds, and drug delivery systems.
[0005] Mineral coatings based on calcium phosphate represent ideal surfaces for biomedical applications because they can be similar to bone tissue in composition and have been shown to promote favorable interactions with natural bone (a property called "bioactivity"). Surface modification techniques associated with mineral coatings attempt to apply an apatite layer with an engineered nanoparticle-grade morphology to the surface of a highly porous biphasic calcium phosphate. It has been demonstrated that mineral-coated surfaces stimulate bone cells, thereby producing an enhanced cellular environment for bone healing. However, since surface technology achieves bone stimulation through the morphological features of nanoparticle size, it is very difficult to control the application of coatings of nanoparticle size and increase the coating surface area. Coatings of bone particles are generally challenging. For example, when bone particles are in granular form, the particles may agglomerate or clump, which generally results in poor bone coatings.
[0006] Sometimes it is necessary to coat bone particles with a nanocoating. Typically, the nanocoating has a thickness of 1 nm to less than 1000 nm. The nanocoating sometimes provides a nanostructure to the bone particles, wherein the surface has a specific nanostructure protruding therefrom and can allow bone remodeling once the bone particles are implanted in the bone defect. Therefore, it would be beneficial to provide methods, devices and compositions for coating bone particles. Summary of the invention
[0007] Methods and apparatus for coating bone particles with a mineral coating that can be effectively applied to the bone particles are provided. The methods and apparatus of the present application utilize at least one mesh. Methods and apparatus for coating bone particles with a nanocoating and / or a nanocoating structure having a specific size and geometry (e.g., a plate-like morphology) to increase the surface area are also provided, which enhances the biological activity of the bone particles and is beneficial to bone remodeling.
[0008] In some embodiments, a method for coating bone particles is provided. The method includes providing a first mesh having a first set of openings to allow a coating liquid and bone particles of a selected size to pass through the first set of openings, and bone particles larger than the selected size are retained on the first mesh; adding bone particles to the first mesh; and contacting the bone particles with the coating liquid to allow bone particles larger than the first set of openings to remain on the first mesh, and allow bone particles smaller than the first set of openings and the coating liquid to pass through the first set of openings, thereby coating the bone particles.
[0009] In some embodiments, a device for coating bone particles is provided. The device includes a first mesh having a first set of openings, the first set of openings being configured to allow a coating liquid and bone particles of a selected size to pass through the first set of openings, and bone particles larger than the selected size are retained on the first mesh; and a housing or container at least partially enclosing the first mesh, the housing or container having an outlet configured to be fluidically coupled to a pump, the pump being configured to provide the coating liquid to at least the first mesh to coat the bone particles.
[0010] In some embodiments, a porous ceramic particle is provided, the porous ceramic particle comprising hydroxyapatite in an amount of about 8 wt % to about 22 wt % and beta-tricalcium phosphate in an amount of about 78 wt % to about 92 wt %. The porous ceramic particle has micropores with an average diameter of about 50 μm to about 800 μm, and each porous ceramic particle has an average particle size of about 0.1 mm to 2.0 mm, the porous ceramic particle has a mineral coating thereon, the mineral coating comprising nanostructures with an average size ranging from about 5 nanometers to about 500 nanometers, wherein the porous ceramic particle has a diameter of about 0.4 m 2 / g to about 9.5m 2 / g of BET surface area.
[0011] Although multiple embodiments are disclosed, other embodiments of the present application will become apparent to those skilled in the art from the following detailed description read in conjunction with the accompanying drawings. It will be apparent that the present disclosure is capable of modification in various obvious aspects, all without departing from the spirit and scope of the present disclosure. Therefore, the specific embodiments are to be regarded as illustrative rather than restrictive in nature. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Other aspects, features, benefits, and advantages of the embodiments will become apparent in part with regard to the following description, appended claims, and accompanying drawings.
[0013] Figure 1A is a top view of one embodiment of a stackable mesh shown in a non-stacked configuration. A single mesh is shown. The mesh includes openings that allow bone particles to be coated in a single layer. Bone particles are not shown.
[0014] Figure 1B is a side view of one embodiment of a stackable mesh. Here, two meshes are shown in a stacked configuration. The opening of the first (top) mesh is larger in size than the opening of the second (lower) mesh. The stackable mesh allows bone particles to be coated as a single layer in each individual mesh.
[0015] Figure 2 is a top view of a single stackable mesh loaded with bone particles and having a coating liquid in contact with the bone particles and floating the bone particles on the mesh, which allows for more surface nucleation of the coating of the bone particles. It should be understood that multiple meshes (not shown) will be stacked below the top mesh shown.
[0016] Figure 3Ais a side view of one embodiment of the apparatus of the present application, which shows the coating of bone particles within a first (top) mesh and a second (bottom) mesh shown in a stacked configuration. The apparatus includes a pump fluidly coupled to a container of a coating liquid, which directs the coating liquid to the first mesh and provides a coating bath to coat the larger bone particles in the first mesh and the smaller bone particles in the second mesh. In this embodiment, excess coating liquid is recycled or replenished.
[0017] Figure 3B 1 is a side view of an embodiment of the apparatus of the present application, which shows the coating of bone particles in a first (top) mesh and a second (bottom) mesh shown in a stacked configuration. The apparatus includes a pump fluidly coupled to a container of a coating liquid, which directs the coating liquid to the first mesh and provides a coating bath to coat the larger bone particles in the first mesh and the smaller bone particles in the second mesh. In this embodiment, both meshes are immersed in the container. In this embodiment, excess coating liquid is also recycled or replenished.
[0018] Figure 4 is a top view of multiple stackable meshes separated in a non-stacked configuration after the coating process is completed. Each mesh has bone particles coated thereon and the mesh can be dried with the bone particles coated thereon. These meshes were initially used in the coating process.
[0019] Figure 5 is a scanning electron micrograph (SEM) of coated bone particles with a mineralized nanoapatite coating.
[0020] Figure 6 This is a photo of bone particles, for example, micrometer-sized before coating. Photograph of a particle (left) and an enhanced photo (25X magnification) of the particle showing macropores and micropores (right).
[0021] Figure 7 is a SEM comparing an uncoated form of bone particles (eg, particles) (left) and a coated form of nanoapatite bone particles (eg, particles) (right).
[0022] Fig. 8A is a SEM showing coated bone particles (eg, particles) using a conventional orbital shaker without implementing the methods and apparatus of the present application.
[0023] Figure 8B is a SEM showing coated bone particles (eg, particles) coated according to one embodiment of the methods and apparatus of the present application.
[0024] It should be understood that the drawings are not drawn to scale. Further, the relationships between objects in the drawings may not be to scale and may actually have opposite relationships with respect to size. The drawings are intended to aid understanding and clarity of the structure of each illustrated object, and therefore, some features may be exaggerated to illustrate specific features of the structure. DETAILED DESCRIPTION
[0025] definition
[0026] For the purpose of this specification and the appended claims, unless otherwise indicated, all digits expressing the amount of components, the percentage or ratio of materials, reaction conditions and other numerical values used in this specification and the claims should be understood to be modified by the term "about" in all cases. Similarly, when a value is expressed as an approximation by using the antecedent "about", it should be understood that the specific value forms another embodiment of + / -10% of the stated value. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximations that can vary depending on the desired properties attempted to be obtained by the present disclosure. Minimally, and without attempting to limit the scope of the application of the doctrine of equivalents to the claims, each numerical parameter should at least be interpreted according to the number of reported significant digits and by applying general rounding techniques. Moreover, as used in the specification and including the appended claims, the singular forms "one", "a" and "said" include plural numbers, and unless the context clearly indicates otherwise, reference to a specific numerical value includes at least the specific value. Ranges may be expressed herein as "about" or "approximately" one particular value and / or "about" or "approximately" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value.
[0027] Although the numerical ranges and parameters setting forth the broad scope of the present application are approximate, the numerical values set forth in the specific examples are reported as accurately as possible. However, any numerical value inherently contains certain errors that are necessarily caused by the standard deviation found in its corresponding test measurements. In addition, all ranges disclosed herein are understood to encompass any and all subranges contained therein. For example, the range "1 to 10" includes any and all subranges between (and including) a minimum value of 1 and a maximum value of 10, i.e., any and all subranges having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10, e.g., 5.5 to 10.
[0028] As used herein, "biocompatible" is intended to describe a material that does not induce undesirable long-term effects when administered in vivo.
[0029] As used herein, "bone" refers to cortical bone, cancellous bone, or cortical-cancellous bone of autologous, allogeneic, xenogeneic, or transgenic origin.
[0030] "Bone particles" include natural bone or synthetic bone or a combination thereof in particle form. Bone particles include natural or synthetic particles, fibers, powders, fragments, chips, demineralized bone particles, surface demineralized bone particles, ceramic particles or a combination thereof. Bone particles, whether natural or synthetic, can be in any shape, including triangles, ellipses, rectangles, spheres, cubes, cylinders or other shapes with regular, irregular or random geometry. The bone particles of the present application can be shaped, freeze-dried, molded, hydrated, made flowable, injected or made into putties or pastes.
[0031] The term "autologous graft" refers to graft material harvested from the same individual patient who is also the recipient of the graft, surgically obtained from a non-essential donor site of the patient.
[0032] As used herein, bone graft refers to any implant prepared according to the embodiments described herein, and thus may include expressions such as bone void fillers.
[0033] The term "macroparticle" or "macroscopic body" includes particles visible to the naked eye. Generally, the length of the macroparticle can be 0.01 mm to about 50 mm. It should be understood that the terms "macroparticle" and "macroscopic body" can be used interchangeably.
[0034] The term "nanoscale features" includes nanometer-sized concave and convex features, or a combination thereof.
[0035] As used herein, the term "osteoinductive" refers to the property of being able to recruit cells from the host that have the potential to stimulate new bone formation. Any material that can induce animal soft tissue to form ectopic bone is considered osteoinductive.
[0036] The term "osteoinduction" refers to the ability to stimulate the proliferation and differentiation of multipotent mesenchymal stem cells (MSCs). In endochondral bone formation, stem cells differentiate into chondroblasts and chondrocytes, forming cartilage ECM, which then calcifies and remodels into lamellar bone. In intramembranous bone formation, stem cells directly differentiate into osteoblasts, which form bone through a direct mechanism. Osteogenic growth factors can stimulate osteoinduction, although some ECM proteins can also drive progenitor cells toward an osteogenic phenotype.
[0037] The term "osteogenesis" refers to the ability of the graft material to generate bone independently. In order to have direct osteogenic activity, the graft must contain cellular components that directly induce bone formation. For example, an allograft seeded with activated MSCs may have the potential to directly induce bone formation without recruiting and activating the host MSC population. Since many osteoconductive allografts can also bind and deliver bioactive molecules, their osteoinductive potential will be greatly improved.
[0038] The term "patient" refers to a biological system to which a treatment can be administered. A biological system can include, for example, an individual cell, a group of cells (e.g., a cell culture), an organ, or a tissue. Additionally, the term "patient" can refer to animals, including but not limited to humans, other primates such as chimpanzees, apes, gorillas, and monkeys, rats, mice, cats, dogs, cows, horses, and the like.
[0039] As used herein, the term "implantable" refers to a biocompatible device (e.g., bone particles) that retains the potential for successful placement in a mammal. As used herein, the expression "implantable composition" and expressions of similar meaning refer to an object that can be implanted by surgery, injection or other suitable means, and the object achieves a primary function through its physical presence or mechanical properties.
[0040] The term "moldable" includes compositions that can be formed by hand or machine or injected into a target tissue site (eg, a bone defect, fracture, or void) into a variety of configurations.
[0041] As used herein, the term "intrinsically cohesive" refers to the tendency of a composition to maintain a unitary, connected quality upon addition of fluids, autologous bone graft, or during manipulation, including exhibiting the ability to be molded or shaped without breaking during manipulation or decomposing or becoming unstable.
[0042] The term "flowable" includes that when the bone particles are mixed with a fluid, they can be administered in an injectable state through a syringe and / or cannula. The bone particles can be flowable when their consistency is fluid-like and their viscosity is lower than the viscosity of the bone particles when they are in the form of putty or paste. Flowable bone particles include liquids or fluids (e.g., solutions, suspensions, etc.) or semisolid compositions (e.g., gels, cements) that are easy to handle and can be brushed, sprayed, dripped, injected, formed, and / or molded at or near the target tissue site. In various embodiments, the bone particles can be used to fill one or more voids in a bone defect (e.g., an osteolytic lesion).
[0043] The terms "hydrate," "hydrate," "hydratable," or "hydrated" refer to an amount of fluid added to bone particles (eg, fibers) to increase the amount of water content in the composition, thereby forming a flowable gel, putty, or paste.
[0044] The term "dehydrated" or "dehydrated" refers to bone particles that contain little or no residual moisture and can be in the form of a dry composition. A dehydrated composition can have a moisture content of about 0% to about 10% based on the total weight of the composition. In some embodiments, when the composition is dehydrated, fluid can be added to the composition to hydrate the composition. Dehydrated compositions include lyophilized or freeze-dried compositions.
[0045] The term "bone marrow aspirate" or "BMA" refers to bone marrow fluid that can be obtained by a syringe and needle to collect bone marrow fluid from a patient. Bone marrow aspirate contains a fluid that contains a heterogeneous mixture of stem and progenitor cells, platelets, and white blood cells. Bone marrow aspirate can be collected from a variety of sources in the body, including, but not limited to, the iliac crest. In some embodiments, BMA can be used to hydrate bone particles.
[0046] Coating method and equipment
[0047] There is a need for methods and apparatus for coating bone particles with mineral coatings that can be effectively applied to the bone particles. It is also useful to use a method and apparatus for coating bone particles with a mineral coating that can provide nano-coating thickness and / or nano-coating structure. Such methods can be automated while increasing the coating surface area and reduce the need for manual manipulation of the material to be coated. There is also a need to produce bone particles with more mineral coatings distributed on the surface of the bone particles to increase the surface area, which enhances the biological activity of the bone particles and facilitates bone remodeling.
[0048] Provided is a method and apparatus for coating bone particles with a mineral coating, which can be effectively applied to bone particles. The method and apparatus of the present application utilizes at least one mesh that can be stacked with one or more meshes. The mesh has a plurality of openings, for passing a plurality of openings through smaller bone particles and a coating liquid, and a larger bone particle larger than the opening stays on the mesh. Usually, a mesh with a larger opening is stacked on a mesh with a smaller opening. In this way, bone particles of a selected size can be contacted with a coating liquid (e.g., incubation, immersion, suspension, soaking, etc.). These bone particles can not only have a coating surface applied to the increase on its surface, but also can carefully control the coating applied to the bone particles. The present application allows to increase the surface exposure of the coating liquid to the bone particle surface, which in turn allows to increase the sporadic mineral nucleation on the bone particle surface.
[0049] In some embodiments, during the coating process, the meshes may have openings of the same size. In some embodiments, the meshes may have openings of different sizes from each other and may be used in the coating process. In some embodiments, meshes may be stacked that do not have bone particles thereon and will allow the coating liquid to pass through their openings.
[0050] In some embodiments, when different sized meshes are used, the different sized meshes also allow different sized bone particles to be isolated on meshes with smaller openings than the bone particles. This allows for reduced waste of bone particles because the bone particles can be captured on the mesh. The mesh also allows for spacing of the bone particles and reduces the chances of bone particles colliding with each other, which can damage the integrity of the coating.
[0051] Figure 1AIt is a top view of an embodiment of a stackable mesh 24 shown in a non-stacked configuration. The first mesh 10 includes a first group of openings 28 that allow bone particles to be coated in a single layer. The first mesh includes a top portion 12, a bottom portion 14, and optionally has a housing 16. As shown, the housing 16 can partially enclose the first mesh, and not only contributes to the stacked mesh, but also allows bone particles to be transferred after being coated in a drying area (e.g., an oven). In some embodiments, the top portion of the first mesh can be configured to have another mesh stacked above it, typically a mesh with larger openings. The top portion 12 of the mesh also has a region where bone particles and a coating liquid can be introduced. In some embodiments, the method only uses a single mesh.
[0052] Figure 1B It is a side view of an embodiment of a stackable mesh. Here, two meshes 30 are shown as a stacked configuration. The first mesh 10 (top mesh) has a first group of openings 28, and the first group of openings is larger in size than the second group of openings 29 of the second mesh 18 (lower mesh). The first mesh includes a top portion 12, a bottom portion 14, and optionally has a shell 16. The top portion 12 of the mesh also has an area where bone particles and coating liquid can be introduced. The second mesh 18 includes a second group of openings 29, and the second group of openings is smaller in size than the first group of openings 28 of the first mesh. The second mesh includes a top portion 20, a bottom portion 26, and optionally has a second shell 22. As shown, the second shell 22 can partially surround the second mesh, and not only helps to stack the second mesh, but also allows bone particles to be transferred after being coated in a drying area (e.g., an oven). In some embodiments, the top portion 20 of the second mesh may have an area where bone particles and coating liquid can be introduced.
[0053] It should be understood that in some embodiments, during the coating process, the mesh can have an opening of the same size as the mesh stacked above or below it. The mesh of the same size can be stacked next to the mesh with the same size opening, or intermittently stacked between different layers of meshes with different size openings. For example, a plurality of meshes with the same size opening can be the first mesh, and these meshes can be stacked next to each other or distributed above or below the mesh with smaller size openings or larger size openings to form a pattern. In some embodiments, the stackable mesh includes a covering mesh 13, which has an opening 15 so that a coating liquid with or without bone particles passes therethrough. The covering mesh can be stacked on the first mesh or can be stacked on all other meshes in the stack. In some embodiments, bone particles may not be present on the covering mesh, and the covering mesh can be used to ensure that the coating liquid flow is the same as the mesh stacked below the covering mesh.
[0054] exist Figure 1BIn the illustrated embodiment, the first mesh is stacked directly above the second mesh, and bone particles having a size larger than the first set of openings of the first mesh are retained thereon for contact with the coating liquid. If the size of the bone particles is larger than the size of the second set of openings of the second mesh, the smaller sized bone particles pass through the first mesh and are captured on the second mesh, where the bone particles will contact the coating liquid passing through the first set of openings of the first mesh.
[0055] Those skilled in the art will appreciate that the meshes may be stacked above or below each other, but need not be in direct contact with each other. Thus, the meshes may be spaced apart from each other by a distance that allows for optimal flow of the coating liquid and particles from one mesh to another. Figure 1B In the embodiment shown, the first mesh shell 16 and the second mesh second shell 22 allow for an optimal distance for bone particles and coating fluid to flow. In some embodiments, the first mesh may be spaced parallel to the second mesh, wherein they are both in fluid communication with each other.
[0056] Figure 2 A top view of a stackable mesh loaded with bone particles 32 is shown, the mesh being in the process of being coated and contacting the bone particles with a coating fluid 34 in the method and apparatus of the present application. Figure 2 In the embodiment of the present invention, bone particles are arranged on the bottom part 14 of the first mesh. The bottom part of the first mesh has a first group of openings 28, which allows smaller bone particles and coating liquid to slowly drain into the second mesh (not shown) and be captured by the second mesh. In this way, by controlling the addition of coating liquid that contacts the bone particles, each individual bone particle is isolated, immersed, suspended and / or incubated in the coating liquid in the top part 12 in the shell 16 of the first mesh 10, and the bone particles can have more coating surfaces. It should be understood that multiple meshes (not shown) can be stacked below the first mesh, including, for example, two, three, four, five, six, seven, eight, nine, ten, eleven, twelve, thirteen, fourteen, fifteen, sixteen, seventeen, eighteen or more meshes. In some embodiments, the term "above" refers to a geographical location at a higher level on the vertical axis. In some embodiments, the term "below" refers to a geographical location at a lower level on the vertical axis. Typically, the meshes are stacked on each other substantially parallel to each other.
[0057] like Figure 2As shown, the bone particles are spaced apart on the mesh, and the mesh allows the bone particles to interact less with each other and maximizes the surface area of the bone particles and the coating liquid. This allows the bone particles to be evenly incubated and coated to form coated bone particles 36 in one layer. It should be understood that the bone particles and the coating liquid can be added to the mesh in any order. Therefore, the bone particles can be added to the mesh first, and then the coating liquid can be added, or the coating liquid can be added to the mesh first, and then the bone particles can be added, or the coating liquid and the bone particles can be added to the mesh at the same time. In some embodiments, the coating liquid and the bone particles can be mixed together and then added to the mesh.
[0058] refer to Figure 3A , provides an apparatus for coating bone particles, the apparatus using at least two meshes that allow bone particles to be coated on each layer of the mesh. Apparatus 62 includes a plurality of stackable meshes (e.g., a first mesh 10 and a second mesh 18). The first mesh has a housing 16 and the second mesh has a second housing 22, and the meshes are shown in a stacked configuration. It will be appreciated by those of ordinary skill in the art that the housing on each mesh is optional.
[0059] Bone particles of various sizes are added to the top portion of the first mesh 10. Large bone particles 42 are captured and placed on the bottom portion 14 of the first mesh. Small bone particles 40 and coating liquid 34 pass through the first set of mesh openings 28 at the bottom portion 14 of the first mesh and flow into the top portion 20 of the second mesh. The small bone particles are then placed on the bottom portion 26 of the second mesh. The bone particles can have various sizes. The size of the large bone particles and the small bone particles is related to the batch of uncoated bone particles to be coated and / or the size of the mesh. For example, as described in Example 1 below, large bone particles with a size greater than 255 microns will stay in the layer on the first mesh. The first mesh may have a first set of openings less than 255 microns. Bone particles with a size less than 255 microns will flow through the first set of openings 28 of the first mesh and flow into the second mesh 18. Smaller bone particles with a size less than 255 microns but greater than 212 microns will stay in the layer of the second mesh. Bone particles and coating fluid having a size less than 212 microns will flow through the second set of mesh openings 29 because they are smaller than the second set of mesh openings and flow into the third mesh layer (not shown).
[0060] In some embodiments, bone particles with a size between 212 microns and 160 microns and all remaining bone particles will be captured and stay on the third mesh in one layer. In some embodiments, bone particles with a size between 212 microns and 160 microns will stay on the layer of the third mesh, and all remaining bone particles and coating liquid will pass through the third mesh and flow into the collection container. In some embodiments, whether the remaining bone particles pass through the bottom layer of the stackable mesh depends on the distribution of the bone particles in each layer, so that the maximum spacing between each particle can be achieved to prevent interference with particle interaction during the mineralization of the coating liquid on the surface of the bone particles.
[0061] In some embodiments, the apparatus further comprises a collection container 31 below or directly below the bottom-most mesh (e.g., the second mesh) such that the second set of openings 29 at the bottom of the second mesh allow smaller bone particles and coating liquid to flow through the second set of openings 29 of the second mesh. The collection container 31 can capture excess coating liquid and / or small bone particles, where they can be recirculated back to the mesh.
[0062] In some embodiments, coating liquid can be added to the stackable mesh to a fill line 38 that indicates the level of coating liquid that can contact the bone particles such that the bone particles can be incubated, immersed, suspended and / or soaked with the coating liquid.
[0063] The mesh allows the bone particles to be spread out or loosely distributed with each other so that each bone particle has a larger surface area exposed to the coating liquid.
[0064] exist Figure 3A In the illustrated device 62, the second housing 22 or the collection container 31 may include an outlet 44 that allows the coating liquid to drain. In the illustrated embodiment, the outlet 44 is disposed on the side wall of the housing (e.g., the second housing 22) or the side wall of the collection container 31. In some embodiments, the outlet includes a filter (not shown) that prevents bone particles from flowing out of the stackable mesh.
[0065] The apparatus 62 may also include a tube 46 fluidly coupled to the outlet 44 at the tube inlet 54, the tube leading to a fluid pump 48, which pumps the collected coating fluid to the tube outlet 56, which delivers the coating fluid back to the stackable mesh. The fluid pump helps pump the fluid from the tube inlet to the tube outlet. In this way, the collected coating fluid can be recirculated back to the mesh to coat the bone particles.
[0066] The apparatus 62 may also include a container 50 for storing the coating liquid. Figure 3A As shown, container 50 has an orifice 52 configured to receive additional or replenishing coating fluid.
[0067] refer to Figure 3B, the second device 63 is similar to Figure 3A Device 62 in the Figure 3B In an embodiment, a second container 58 is provided. The container is connected to the tube and is capable of replenishing additional coating liquid into the stackable mesh. In some embodiments, the device also includes a second container 58. The second container 58 is configured to accommodate and partially enclose the stackable mesh. The second container 58 may include an outlet 60 of the second container. The outlet 60 of the second container may be disposed on the side wall 59 of the second container. The outlet 60 may be aligned with the outlet 44 (not shown) of the second shell 22. This allows the outlet to discharge the coating liquid to the tube 46, which is fluidly connected to the pump 48, which pumps the coating liquid out to the outlet 56. The device allows for recycling or replenishing of the coating liquid. Figure 3B In the illustrated embodiment, the first mesh and the second mesh are immersed in the coating liquid in the second container. In some embodiments, the container is configured to enclose at least the first mesh, at least the second mesh, or at least the first mesh and the second mesh.
[0068] In some embodiments, the method and apparatus of the present application can be continued by continuously pumping and discharging the coating liquid from the bottom shell of the second container and / or the stackable mesh. In some embodiments, the method can be carried out in a batch process so that the coating liquid is completely discharged before adding new and / or unused coating liquid back into the second container or into the first mesh. In some embodiments, the apparatus may include a weight 11 located above and / or above the first mesh to prevent the first mesh from overflowing or moving in the second container. The weight can be in various shapes that do not interfere with the addition of the coating liquid and / or bone particles.
[0069] After coating the bone particles, the mesh can be removed and the mesh containing the bone particles can be placed directly in an oven for drying without transferring the coated bone particles from the mesh.
[0070] Figure 4 An embodiment of a stackable mesh is shown in a non-stacked configuration. The stackable mesh provides the benefit of easy transfer and drying of coated bone particles 68. The coated bone particles can be dried directly on the mesh used to capture and coat the bone particles. Figure 4 The drying mesh 66 and the outlet 67 of the housing are shown. Figure 5 As shown in the scanning electron micrograph (SEM) in , the resulting coated bone particles have a nanoapatite coating on their surface, which increases the surface area of the bone particles. In some embodiments, the method includes drying the coated bone particles retained on the first mesh, the second mesh, the third mesh, or all meshes in an oven.
[0071] Bone particles
[0072] Bone particles that can be added to the mesh for coating can include natural bone or synthetic bone in particle form and can be coated with a polymer (e.g., collagen) before coating with a liquid coating. Bone particles include natural or synthetic particles, fibers, powders, fragments, fragments, demineralized bone particles, surface demineralized bone particles, ceramic particles, or combinations thereof. Bone particles, whether natural or synthetic, can be any shape, including triangles, ellipses, rectangles, spheres, cubes, cylinders, discs, or other shapes with regular, irregular, or random geometries.
[0073] In some embodiments, the bone particles that can be added to the mesh for coating can be inorganic materials, such as inorganic ceramics and / or bone substitute materials. Exemplary inorganic materials or bone substitute materials include, but are not limited to, aragonite, feldspar, calcite, brushite, amorphous calcium carbonate, vaterite, keystone, charophyte, struvite, urate, ferrihydrite, cristobalite, diaspore, magnetite, goethite, dentin, calcium carbonate, calcium sulfate, calcium phosphosilicate, sodium phosphate, calcium aluminate, calcium phosphate, hydroxyapatite, α-tricalcium phosphate, dicalcium phosphate, β-tricalcium phosphate, tetracalcium phosphate, amorphous calcium phosphate, octacalcium phosphate, BIOGLASS TM Fluorapatite, chlorapatite, magnesium-substituted tricalcium phosphate, carbonate hydroxyapatite, substituted forms of hydroxyapatite (e.g., hydroxyapatite derived from bone can be substituted with other ions, such as fluoride, chloride, magnesium, sodium, potassium, etc.), or combinations or derivatives thereof.
[0074] In some embodiments, the bone particles that can be added to the mesh for coating can include mineral particles that include tricalcium phosphate and hydroxyapatite in a ratio of about 80:20 to about 90:10. In some embodiments, the mineral particles can include tricalcium phosphate and hydroxyapatite in a ratio of about 70:30 to about 95:5. In some embodiments, the mineral particles can include tricalcium phosphate and hydroxyapatite in a ratio of about 85:15.
[0075] The bone particles that can be added to the mesh for coating can have a certain size distribution. The most widely used method to describe the bone particle size distribution is the D value. D10, D50 and D90 values are generally used to represent the midpoint and range of the bone particle size of a given sample. In particular, the bone particle size distribution D50 is also called the median length or diameter or median of the bone particle size distribution; it is the value of the bone particle diameter at 50% in the cumulative distribution, D10 is the size of the bone particle sample below which 10% of the sample is located, and D90 is the size of the bone particle sample below which 90% of the sample is located. In some embodiments, the D50 value of the bone particles is in the range of 50 microns to 250 microns.
[0076] In some embodiments, the bone particles that can be added to the mesh screen for coating can have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. In some embodiments, the bone particles have a D10, D50, or D90 size of 250 microns or less. , 70 microns, 72 microns, 74 microns, 76 microns, 78 microns, 80 microns, 82 microns, 84 microns, 86 microns, 88 microns, 90 microns, 92 microns, 94 microns, 96 microns, 98 microns, 100 microns, 102 microns, 104 microns, 106 microns, 108 microns, 110 microns, 112 microns, 114 microns, 116 microns, 118 microns, 120 microns, 122 microns, 124 microns, 126 microns, 128 microns, 130 microns, 132 microns, 134 microns 34 microns, 136 microns, 138 microns, 140 microns, 142 microns, 144 microns, 146 microns, 148 microns, 150 microns, 152 microns, 154 microns, 156 microns, 158 microns, 160 microns, 162 microns, 164 microns, 166 microns, 168 microns, 170 microns, 172 microns, 174 microns, 176 microns, 178 microns, 180 microns, 182 microns, 184 microns, 186 microns, 188 microns, 190 microns, 192 microns, 194, 196, 198, 200, 202, 204, 206, 208, 210, 212, 214, 216, 218, 220, 222, 224, 226, 228, 230, 232, 234, 236, 238, 240, 242, 244, 246, 248 and / or 250 microns.
[0077] In one embodiment, suitable bone particles that can be incorporated into the mesh and coated with the coating fluid include those manufactured by Medtronic Sofamor Danek, Inc., Memphis, Tennessee. Particles and Microparticles, which are biphasic, resorbable ceramic particles, contain about 15% hydroxyapatite (HA) and about 85% beta-tricalcium phosphate (β-TCP). The particles have a natural, interconnected porous structure that mimics the natural structure of bone and allows for rapid, uniform ingrowth of bone in each particle. Each particle is about 80% porous, with an average pore size of about 500 microns and an interconnection diameter of about 125 microns. The average diameter of the particles is from about 1.6 mm to about 3.2 mm. In some embodiments, the average diameter of the particles may be from about 0.1 mm to about 0.8 mm. The average diameter of the small particles is about 0.5 mm to about 1.6 mm. Through the highly porous particle structure and 15% HA / 85% β-TCP chemical composition, Particles and The small particles promote rapid, uniform bone fusion, which supports the bone healing process by acting as a scaffold on which bone can grow. The porosity of the material provides an excellent foundation for vascularization and infiltration of relevant cells, which supports the integration of replacement materials required for healing while preserving bone structure and attached gingiva.
[0078] Figure 6 It is micron-level before coating Photograph of particle 70 (left) and an enhanced photograph (25X magnification) of the particle showing macropores 72 and micropores 74 (right).
[0079] In some embodiments, the diameter of the bone particles to be coated or the macropores of the coated bone particles can be from about 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195 μm, 200 μm, 205 μm, 210 μm, 215 μm, 220 μm, 225 μm, μm, 230μm, 235μm, 240μm, 245μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm , 325μm, 330μm, 335μm, 340μm, 345μm, 350μm, 355μm, 360μm, 365μm, 370 μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm, 405μm, 410μm, 415μm, 42 0μm, 425μm, 430μm, 435μm, 440μm, 445μm, 450μm, 455μm, 460μm, 465μm, 470μm, 475μm, 480μm, 485μm, 490μm, 495μm, 500μm, 505μm, 510μm, 515μm m, 520μm, 525μm, 530μm, 535μm, 540μm, 545μm, 550μm, 555μm, 560μm, 565μm, 570μm, 575μm, 580μm, 585μm, 590μm, 595μm, 600μm, 605μm, 610μm, 615μm, 620μm, 625μm, 630μm, 635μm, 640μm, 645μm, 650μm, 655μm, 660μ m, 665μm, 670μm, 675μm, 680μm, 685μm, 690μm, 695μm, 700μm, 705μm, 71 0μm, 715μm, 720μm, 725μm, 730μm, 735μm, 740μm, 745μm, 750μm, 755μm, In the range of 760μm, 765μm, 770μm, 775μm, 780μm, 785μm, 790μm, 795μm to about 800μm.In some embodiments, the diameter of each of the micropores can be about 0.01 micrometers, 0.02 micrometers, 0.03 micrometers, 0.04 micrometers, 0.05 micrometers, 0.06 micrometers, 0.07 micrometers, 0.08 micrometers, 0.09 micrometers, 0.1 micrometers, 0.2 micrometers, 0.3 micrometers, 0.4 micrometers, 0.5 micrometers, 0.6 micrometers, 0.7 micrometers, 0.8 micrometers, 0.9 micrometers, 1 micrometer, 2 micrometers, 3 micrometers, 4 micrometers, 5 micrometers, 6 micrometers, 7 micrometers, 8 micrometers, 9 micrometers to about 10 micrometers.
[0080] In some embodiments, the bone particles to be coated or the coated bone particles may have a microporosity percentage of about 10% to about 100% or about 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% to about 100%. In some embodiments, the micropores may have a diameter ranging from about 50 μm to about 800 μm.In some embodiments, the micropore diameter is between about 10μm、20μm、30μm、40μm、50μm、60μm、70μm、80μm、90μm、100μm、105μm、110μm、115μm、120μm、125μm、130μm、135μm、140μm m、145μm、150μm、155μm、160μm、165μm、170μm、175μm、180μm、185μm、190μm、195μm、200μm、205μm、210μm、215μm、220μm、225μm、230μm、235μm m, 240μm, 245μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm, 405μm, 410μm, 415μm, 420μm, 425μm m、430μm、435μm、440μm、445μm、450μm、455μm、460μm、465μm、470μm、475μm、480μm、485μm、490μm、495μm、500μm、505μm、510μm、515μm、520μm m、525μm、530μm、535μm、540μm、545μm、550μm、555μm、560μm、565μm、570μm、575μm、580μm、585μm、590μm、595μm、600μm、605μm、610μm、615μm m, 620μm, 625μm, 630μm, 635μm, 640μm, 645μm, 650μm, 655μm, 660μm, 665μm, 670μm, 675μm, 680μm, 685μm, 690μm, 695μm, 700μm, 705μm, 710μm, 715μm, 720μm, 725μm, 730μm, 735μm, 740μm, 745μm, 750μm, 755μm, 760μm, 765μm, 770μm, 775μm, 780μm, 785μm, 790μm, 795μm to about 800μm.
[0081] In some embodiments, the bone particles to be coated may include ceramic material in an amount of about 50% to about 98% by weight based on the total weight of each bone particle and polymer in an amount of about 2% to about 50% by weight, as described in more detail in U.S. patent application serial number 17 / 018,708, filed on September 11, 2020 and assigned to Warsaw Orthopaedics, Inc., published as US20210069382, the entirety of which is incorporated herein by reference. Based on the total weight of each bone particle, the plurality of bone particles may each include from about 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126%, 127%, 128%, 129%, 13 %, 72 wt%, 73 wt%, 74 wt%, 75 wt%, 76 wt%, 77 wt%, 78 wt%, 79 wt%, 80 wt%, 81 wt%, 82 wt%, 83 wt%, 84 wt%, 85 wt%, 86 wt%, 87 wt%, 88 wt%, 89 wt%, 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, % to about 98 wt % of a ceramic material and from about 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20 wt %, 21 wt %, 22 wt %, 23 wt %, 24 wt %, 25 wt %, %, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt%, 40 wt%, 41 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt%, 49 wt% to about 50 wt% of a polymer. The ceramic material may include a synthetic ceramic or a ceramic including hydroxyapatite and beta-tricalcium phosphate. The ceramic material may be in powder form. The ceramic material may include a ratio of calcium to phosphate between 1.0 to about 2.0. In some embodiments, the ratio of calcium to phosphate is between 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 to about 2.0.
[0082] The ceramic material of the bone particles can be a biphasic calcium phosphate comprising hydroxyapatite in an amount of about 8% to about 22% by weight and beta-tricalcium phosphate in an amount of about 78% to about 92% by weight. In some embodiments, the amount of hydroxyapatite is about 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21% to about 22% by weight, and the amount of tricalcium phosphate is about 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91% to about 92% by weight.
[0083] The porous ceramic particles may include hydroxyapatite and β-tricalcium phosphate. Based on the total weight of the ceramic particles, the amount of hydroxyapatite may be about 8 wt % to about 22 wt %. The hydroxyapatite may be in the range of about 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20 wt %, 21 wt % to about 22 wt %. In some embodiments, the hydroxyapatite may be in the range of about 1 wt % to about 99 wt %, such as about 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20 wt %, 21 wt %, 22 wt %. 2 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt%, 40 wt%, 41 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt%, 8 wt%, 49 wt%, 50 wt%, 51 wt%, 52 wt%, 53 wt%, 54 wt%, 55 wt%, 56 wt%, 57 wt%, 58 wt%, 59 wt%, 60 wt%, 61 wt%, 62 wt%, 63 wt%, 64 wt%, 65 wt%, 66 wt%, 67 wt%, 68 wt%, 69 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 4 wt %, 75 wt %, 76 wt %, 77 wt %, 78 wt %, 79 wt %, 80 wt %, 81 wt %, 82 wt %, 83 wt %, 84 wt %, 85 wt %, 86 wt %, 87 wt %, 88 wt %, 89 wt %, 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt %, 97 wt %, 98 wt % to about 99 wt %.
[0084] Based on the total weight of the ceramic particles, the amount of β-tricalcium phosphate can be from about 78% to about 92% by weight. The amount of β-tricalcium phosphate can be from about 78% by weight, 79% by weight, 80% by weight, 81% by weight, 82% by weight, 83% by weight, 84% by weight, 85% by weight, 86% by weight, 87% by weight, 88% by weight, 89% by weight, 90% by weight, 91% by weight to about 92% by weight. In some embodiments, the β-tricalcium phosphate can be in the range of from about 1% by weight to about 99% by weight, for example, from about 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 8 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt%, 40 wt%, 41 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt%, 49 wt%, 50 wt%, 51 wt%, 52 wt%, 53 wt%, 54 wt%, 55 wt%, 56 wt%, 57 wt%, 58 wt%, 59 wt%, 60 wt%, 61 wt%, 62 wt%, 63 wt%, 64 wt%, 65 wt%, 66 wt%, 67 wt%, 68 wt%, 69 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 75 wt%, 76 wt%, 77 wt%, 78 wt%, 79 wt%, 80 wt%, 81 wt%, 82 wt%, 83 wt%, 84 wt%, 85 wt%, 86 wt%, 87 wt%, 88 wt%, 89 wt%, 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, 98 wt% to about 99 wt%.
[0085] The porous ceramic particles can have a calcium to phosphate ratio between 1.0 and about 2.0. In some embodiments, the calcium to phosphate ratio is between 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and about 2.0.
[0086] In some embodiments, ceramic particles coated with a coating fluid (e.g., a mineral coating) can be embedded in a porous carrier matrix, such as cross-linked or non-cross-linked collagen, carboxymethyl cellulose, or alginate, which can also include an identifier or surface marker that distinguishes them from uncoated ceramic particles.
[0087] The polymer component of each of the plurality of bone particles can be porcine or bovine collagen, bovine type I collagen, tendon or dermis derived collagen, or combinations thereof.
[0088] Each of the plurality of bone particles to be coated with the coating liquid or coated with the coating liquid may have an average diameter of about 0.1 mm to about 10 mm. For example, the average diameter of each of the bone particles may be about 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.1 mm, 3.2 mm, 3.3 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.1 mm, 4.2 mm, 4.3 mm, 4.4 mm, 4.5 mm, 4.6 mm, 4.7 mm, 4.8 mm, 4.9 mm, 5. .2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, 3mm, 3.1mm, 3.2mm, 3.3mm, 3.4mm, 3 .5mm, 3.6mm, 3.7mm, 3.8mm, 3.9mm, 4mm, 4.1mm, 4.2mm, 4.3mm, 4.4mm, 4.5mm, 4.6mm, 4.7mm, 4. 8mm, 4.9mm, 5mm, 5.1mm, 5.2mm, 5.3mm, 5.4mm, 5.5mm, 5.6mm, 5.7mm, 5.8mm, 5.9mm, 6mm, 6.1m m, 6.2mm, 6.3mm, 6.4mm, 6.5mm, 6.6mm, 6.7mm, 6.8mm, 6.9mm, 7mm, 7.1mm, 7.2mm, 7.3mm, 7.4mm , 7.5mm, 7.6mm, 7.7mm, 7.8mm, 7.9mm, 8mm, 8.1mm, 8.2mm, 8.3mm, 8.4mm, 8.5mm, 8.6mm, 8.7mm, 8.8mm, 8.9mm, 9mm, 9.1mm, 9.2mm, 9.3mm, 9.4mm, 9.5mm, 9.6mm, 9.7mm, 9.8mm, 9.9mm to about 10mm. In some embodiments, the bone particles can have a particle size of about 0.09mm to about 0.8mm.
[0089] The average height and / or length of each bone particle in the bone fiber to be coated with the coating liquid or coated with the coating liquid can be about 0.05mm, 0.01mm to about 10mm or about 0.01mm, 0.02mm, 0.03mm, 0.04mm, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm to about 10mm.
[0090] The ceramic material in each bone particle to be coated with the coating liquid or each bone particle coated with the coating liquid may be in the form of porous ceramic particles. Exemplary porous ceramic particles suitable for the present application include particles described in U.S. Application Serial No. 16 / 523,259, disclosed as US20210023258A1, filed on July 26, 2019 and assigned to Warsaw Orthopaedics, Inc., the entire contents of which are incorporated herein by reference. The average diameter of the porous ceramic particles to be coated with the coating liquid or coated with the coating liquid may be about 50 μm to 1.6 mm. In some embodiments, the particles may have an average diameter of about 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195 μm, 200 μm, 205 μm, 210 μm, 220 μm, 235 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm , 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350μm, 355μm, 360μm, 365μm, 370μm, 375μm m, 380μm, 385μm, 390μm, 395μm, 400μm, 405μm, 410μm, 415μm, 420μm, 425μm, 430μm, 435μm, 440μm, 445μm, 450μm, 455μm, 460 μm, 465μm, 470μm, 475μm, 480μm, 485μm, 490μm, 495μm, 500μm, 505μm, 510μm, 515μm, 520μm, 525μm, 530μm, 535μm, 540μm, 54 5μm, 550μm, 555μm, 560μm, 565μm, 570μm, 575μm, 580μm, 585μm, 590μm, 595μm, 600μm, 605μm, 610μm, 615μm, 620μm, 625μm, 6 30μm, 635μm, 640μm, 645μm, 650μm, 655μm, 660μm, 665μm, 670μm, 675μm, 680μm, 685μm, 690μm, 695μm, 700μm, 705μm, 710μm,715μm, 720μm, 725μm, 730μm, 735μm, 740μm, 745μm, 750μm, 755μm, 760μm, 765μm, 770μm, 775μm, 780μm, 785μm, 790μm, 795μm, 800 μm, 850μm, 900μm, 950μm, 1000μm, 1100μm, 1150μm, 1200μm, 1250μm, 1300μm, 1350μm, 1400μm, 1450μm, 1500μm, 1550μm to about 1600μm. ,
[0091] Each porous ceramic particle to be coated with the coating liquid or already coated with the coating liquid may have a particle size of about 0.2 μm. 2 / g to about 10m 2 / g Brunauer-Emmett-Teller (BET) surface area. The BET surface area can be about 0.2 m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m 2 / g、27m 2 / g、28m 2 / g、29m 2 / g、30m 2 / g、31m 2 / g、32m 2 / g、33m 2 / g、34m 2 / g、35m 2 / g、36m 2 / g、37m 2 / g、38m 2 / g、39m 2 / g、40m 2 / g、41m 2 / g、42m 2 / g、43m 2 / g、44m 2 / g、45m 2 / g、46m 2 / g、47m 2 / g、48m 2 / g、49m 2 / g、50m 2 / g、51m 2 / g、52m 2 / g、53m 2 / g、54m 2 / g、55m 2 / g、56m 2 / g、57m 2 / g、58m 2 / g、59m 2 / g、60m 2 / g、61m 2 / g、62m 2 / g、63m 2 / g、64m 2 / g、65m 2 / g、66m 2 / g、67m 2 / g、68m 2 / g、69m 2 / g、70m 2 / g、71m 2 / g、72m 2 / g、73m 2 / g、74m 2 / g、75m 2 / g、76m 2 / g、77m 2 / g、78m 2 / g、79m2 / g, 80m 2 / g, 81m 2 / g, 82m 2 / g, 83m 2 / g, 84m 2 / g, 85m 2 / g, 86m 2 / g, 87m 2 / g, 88m 2 / g, 89m 2 / g, 90m 2 / g, 91m 2 / g, 92m 2 / g, 93m 2 / g, 94m 2 / g, 95m 2 / g, 96m 2 / g, 97m 2 / g, 98m 2 / g, 99m 2 / g to about 100m 2 / g. The increase in surface area further promotes new bone growth by causing the particles to dissolve and release calcium faster than ordinary particles.
[0092] Each porous ceramic particle to be coated with a coating liquid or coated with a coating liquid may have microporosity, and the diameter of the micropores is about 0.01 micron to about 10 microns. In some embodiments, the diameter of each micropore in the micropores can be about 0.01 micron, 0.02 micron, 0.03 micron, 0.04 micron, 0.05 micron, 0.06 micron, 0.07 micron, 0.08 micron, 0.09 micron, 0.1 micron, 0.2 micron, 0.3 micron, 0.4 micron, 0.5 micron, 0.6 micron, 0.7 micron, 0.8 micron, 0.9 micron, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns to about 10 microns. In some embodiments, the median pore size can be about 125 μm, and the average pore size can be 78 μm.
[0093] A plurality of bone particles to be coated with a coating liquid or already coated with a coating liquid can be made into various shapes after freeze drying or using cryogel coating. These shapes can be cut from a textured or flat-shaped bone particle sheet comprising a ceramic material and a polymer, or can be prepared as individual bone particles produced in a mold.
[0094] The bone particles to be coated with the coating fluid or coated with the coating fluid are porous, but in some embodiments, the bone particles are highly porous. For example, the porosity of the porous bone particles can be from about 10% to about 80% or from about 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 2%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% to about 80%. The porosity of high porosity bone particles may be about 81% to about 99% or about 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% to about 99%.
[0095] In some embodiments, additional or alternative materials can be added to the bone particles after the bone particles are coated with the coating liquid, such as one or more of the following: poly (α-hydroxy acid), polyglycolide (PG), polyethylene glycol (PEG) conjugates of poly (α-hydroxy acid), polyorthoesters (POE), polyaspirins, collagen, polyphosphagenes, gelatin, hydrolyzed gelatin, fractions of hydrolyzed gelatin, elastin, starch, pregelatinized starch, hyaluronic acid, chitosan, alginate, albumin, fibrin, vitamin E analogs such as α-tocopheryl acetate, d-α-tocopheryl succinate, D,L-lactide or L-lactide, caprolactam, cellulose, cellulose acetate, cellulose esters ... Esters, dextran, vinyl pyrrolidone, polyvinyl alcohol (PVA), PVA-g-PLGA, PEGT-PBT copolymer (polyactive), methacrylate, PEO-PPO-PAA copolymer, PLGA-PEO-PLGA, PEG-PLG, PLA-PLGA, poloxamer 407, PEG-PLGA-PEG triblock copolymer, POE, SAIB (sucrose acetate isobutyrate), polydioxanone, methyl methacrylate (MMA), MMA and N-vinyl pyrrolidone, polyamide, oxidized cellulose, copolymer of glycolic acid and trimethylene carbonate, polyesteramide, polyetheretherketone, polymethyl methacrylate, silicone, hyaluronic acid or a combination thereof.
[0096] In some embodiments, the bone particles after coating with the coating liquid may include at least one biodegradable polymer, which includes one or more of the following: collagen, poly(lactide-co-glycolide) (PLGA), polylactide (PLA), polyglycolide (PGA), D-lactide, D,L-lactide, L-lactide, D,L-lactide-co-ε-caprolactone, L-lactide-co-ε-caprolactone, D,L-lactide-co-glycolide-co-ε-caprolactone, poly(D,L-lactide-co-caprolactone), poly(L-lactide-co-caprolactone), poly(D-lactide-co-caprolactone), poly(D,L-lactide), poly(D-lactide), poly(L-lactide), poly(esteramide), carboxymethylcellulose (CMC), alkylene oxide copolymer (AOC), or a combination thereof.
[0097] The collagen added to the coated bone particles can be from skin, tendon, fascia, ligament, trachea or organ collagen. In certain embodiments, the collagen is human collagen or another mammal collagen (e.g., porcine, bovine or ovine). The collagen can be derived from any animal.
[0098] Generally, about twenty-eight different collagen types have been identified in vertebrates (including bovine, ovine, porcine, chicken, marine and human sources). The collagen types are numbered with Roman numerals, and the chains found in each collagen type are identified with Arabic numerals. Detailed descriptions of the structures and biological functions of the various types of naturally occurring collagen are generally available in the art.
[0099] The collagen can have the same composition as naturally occurring source.The example of collagen source includes people or non-human (cow, sheep and / or pig), and recombinant collagen or their combination.The example of suitable collagen includes but is not limited to people I collagen, people II collagen, people III collagen, people IV collagen, people V collagen, people VI collagen, people VII collagen, people VIII collagen, people IX collagen, people X collagen, people XI collagen, people XII collagen, people XIII collagen, people XIV collagen, people XV collagen, people XVI collagen, people XVII collagen, people XVIII collagen, people XIX collagen, people XXI collagen, people XXII collagen, people XXIII collagen, people XXIV collagen, people XXV collagen, people XXVI collagen, people XXVII collagen and people XXVIII collagen, or their combination. Collagen can also or alternatively comprise heterotrimers and homotrimers of any of the above-mentioned collagen types. In some embodiments, collagen comprises heterotrimers or homotrimers of human type I collagen, human type II collagen, human type III collagen, or a combination thereof. In some embodiments, collagen is type I or substantially all type I collagen, for example, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90% or at least 95%.
[0100] Coating liquid
[0101] The coating liquid applied to the bone particles imparts an increased surface area to the bone particles. In some embodiments, the increased surface area increases the hydrophilic nature of the coated bone particles and makes the bone implant formed from those coated bone particles more hydrophilic and more osteoinductive and osteoconductive, thereby allowing the implant to better fuse with the bone defect.
[0102] The coating liquid is flowable and can be contacted with the bone particles in a controlled manner by incubating, immersing, suspending and / or soaking the coating liquid in those bone particles. The coating liquid can include a mineral component, a polymer component, an organic component, a solvent, a buffer, or a combination thereof.
[0103] In some embodiments, the coating solution comprises a calcium-containing mineral, which is at least one of apatite, hydroxyapatite (HAP), α-tricalcium phosphate, β-tricalcium phosphate, amorphous calcium phosphate, dicalcium phosphate, octacalcium phosphate, calcium carbonate, carbonate-substituted calcium-deficient hydroxyapatite, inorganic bone, or a combination thereof. Inorganic bone refers only to bone mineral with organic components removed.
[0104] Calcium-containing minerals can include multiple layers, such as separated layers with different dissolution curves. Under physiological conditions, the solubility of calcium phosphate materials can follow the following solubility trend: amorphous calcium phosphate> dicalcium phosphate> octacalcium phosphate> β-TCP> HAP. The dissolution rate of dicalcium phosphate minerals can be more than fifty times the dissolution rate of HAP. Therefore, the generation of substrates with different calcium phosphate coatings allows a wide range of dissolution patterns.
[0105] The mineral coating may impart spherical clusters of bone particles with a plate-like structure or a plate-like structure and a carbonate-substituted calcium-deficient hydroxyapatite phase structure. As another example, the coating may be an osteoconductive mineral coating and allow osteoclasts and osteoblasts to remodel the bone.
[0106] The mineral coating that can be used to coat the bone particles can include a porosity of at least about 1% or at least about 100%, including all discrete values included in this range. The mineral coating can also include a pore size of about 1 nm to about 3500 nm, including all discrete values included in this range. The mineral coating that can be used for the present application can include a ratio of at least about 0.1 Ca / P to about 10 Ca / P, including discrete values included in this range.
[0107] As another example, the mineral coating can include apatite or amorphous apatite. The apatite can include calcium phosphate, calcium carbonate, calcium fluoride, calcium hydroxide, calcium citrate, or a combination thereof.
[0108] As another example, the mineral coating can include a plurality of discrete mineral islands on the bone particles, or the mineral coating can be formed over the entire surface of the bone particles. As another example, the mineral coating can include a substantially uniform mineral coating. In other embodiments, the mineral coating can be calcium-deficient carbonate-containing hydroxyapatite.
[0109] As another example, the mineral coating may include hydroxyapatite. Calcium-deficient (non-stoichiometric) hydroxyapatite Ca 10x (PO4) 6-x (HPO4) x (OH) 2x (where x is between 0 and 1) has a Ca / P ratio between 1.67 and 1.5. The Ca / P ratio is often used in discussions of calcium phosphate phases. The stoichiometric apatite Ca 10 (PO4)6(OH)2 has a Ca / P ratio of 10:6, usually expressed as 1.67. The non-stoichiometric phase has cation vacancies (Ca 2+ ) and anions (OH -) vacant hydroxyapatite structure. Hydroxyapatite can be primarily crystalline, but in some cases, can exist in an amorphous form. The mineral coatings useful for the present application can contain at least about 1% to at least about 100% hydroxyapatite, including discrete values included in this range.
[0110] It is well known that hydroxyapatite in the bones of living organisms is a very thin plate-like carbonate structure having an average length of 50 nm, an average thickness of 2 nm-3 nm, and an average width of 25 nm (see, e.g., Heliyon, Vol. 6, No. 4, 2020, Article e03655). In some embodiments, the surface coating on the bone particles is designed to have these properties.
[0111] In some embodiments, the mineral coating may include octacalcium phosphate. Octacalcium phosphate has the chemical formula Ca8H2(PO4)65H2O, or it may also be written as Ca4HO 12 P3. Octacalcium phosphate has been demonstrated to be a precursor to hydroxyapatite. Hydrolysis of octacalcium phosphate can produce hydroxyapatite. Octacalcium phosphate can be primarily crystalline, but in some cases, can exist in an amorphous form. In some embodiments, the mineral coating can include at least about 1% to at least about 100% octacalcium phosphate, including discrete values included within this range.
[0112] In some embodiments, prior to coating the bone particles, the bone particles are first cleaned, rinsed in an alkaline bath, and then contacted (eg, incubated, immersed, suspended, and / or soaked) with a coating fluid, which may comprise modified simulated body fluid (mSBF).
[0113] The method for preparing the mSBF coating liquid that can be used for the present application is described in U.S. application serial number 15 / 060,547, which was assigned to Warsaw Orthopedics and disclosed as US20160271296A1 and submitted on March 3, 2016, and is described in U.S. patent application serial number 13 / 879,178, which was assigned to Warsaw Orthopedics and disclosed as US20140161886A1 and submitted on September 25, 2009. These entire disclosures are incorporated herein by reference in their entirety and describe how to manufacture a mineral coating with a plate-like nanostructure on a substrate. These patent applications also describe the formation of a plate-like nanostructure comprising nanoparticles having a size range of about 100 nanometers to about 500 nanometers.
[0114] In some embodiments, the plate-like nanostructures on the coated bone particles comprise nanostructures having a size range of about 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 205 nm, 210 nm, 215 nm, 220 nm In some embodiments, the plate-like nanostructures on the coated bone particles include nanoparticles having a size range of about 5 nanometers to about 500 nanometers. In some embodiments, the plate-like nanostructures on the coated bone particles include nanoparticles having a size range of about 50 nanometers to about 200 nanometers. In some embodiments, the plate-like nanostructures on the coated bone particles include nanoparticles having a size range of about 100 nanometers to about 200 nanometers. mSBF provides a calcium- and phosphate-rich environment to promote crystallization.
[0115] In one embodiment, the bone particles include those manufactured by Medtronic SofamorDanek, Inc. of Memphis, Tennessee. The particles are biphasic, resorbable ceramic particles containing about 15% hydroxyapatite (HA) and about 85% beta-tricalcium phosphate (β-TCP). The particles have a natural, interconnected porous structure that mimics the natural structure of bone and allows for rapid, uniform ingrowth of bone in each particle. Each particle is about 80% porous, with an average pore size of about 500 microns and an interconnection diameter of about 125 microns.
[0116] For coating Particles, they are suspended in the coating liquid, and the coating liquid can be mSBF. The recirculating bath is used to maintain physiological temperature, and ensures that the controlled interaction rate between mSBF and particles occurs during the whole coating process. Stackable mesh increases the material density in the container while maintaining mSBF flowing around the particles. mSBF can be updated every day, for example, for three days, then rinsed with water and dried. In some embodiments, mSBF is updated at a frequency of about every 1 hour to every 12 hours. In some embodiments, mSBF is updated at a frequency of about every 1 hour, every 2 hours, every 3 hours, every 4 hours, every 5 hours, every 6 hours, every 7 hours, every 8 hours, every 9 hours, every 10 hours, every 11 hours, every 12 hours, every 13 hours, every 14 hours, every 15 hours, every 16 hours, every 17 hours, every 18 hours, every 19 hours, every 20 hours, every 21 hours, every 22 hours, every 23 hours to about every 24 hours. In some embodiments, mSBF is updated once every 2 hours.
[0117] Once the coating is complete, the mesh allows the coated particles to be transferred directly to an oven for drying. Thus, the individual particles are prevented from interacting with each other and interfering with the growth of the nanoapatite plates coated on the particles. The coating on the surface of the bone particles can be a nano-sized coating with a nano-coating thickness and / or a nano-coating structure.
[0118] In some embodiments, the range of nanocoating thickness is from about 1 nm to about 1000 nm. In some embodiments, the range of thickness is from about 50 nm to about 200 nm. In some embodiments, the range of thickness is from about 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 205 nm, 210 nm, 215 nm to about 220 nm.
[0119] In some embodiments, the liquid coating can be a mineral coating (eg, mSBF) that also contains a polymer and a solvent. The polymer can be an acrylic resin, alginate, caprolactone, collagen, deacetylated chitosan, hyaluronic acid, a hydrogel, hydroxybutyric acid, a polyanhydride, polycaprolactone (PCL), poly(dimethylglycolic acid), polydioxanone (PDO), polyester, polyethylene, poly(ethylene glycol), poly(glycolide) (PGA), poly(glycolic acid), polyhydroxybutyrate, poly(2-hydroxyethyl methacrylate), poly-lactide-co-glycolide (PLCG), poly(D,L-lactide-co-glycolide) (PLG), poly(lactide-co-glycolic acid) (PLGA), polylactide (PLA), polylactic acid (PLLA), poly-lactide-co-glycolide (PLCG), poly(methyl ethyl glycolic acid), polymethyl methacrylate, polyphosphazene, polyphosphate, polypropylene, poly(propylene fumarate), polyurethane (PU) or silicone rubber, or a combination or copolymer thereof. In some embodiments, the polymer in the mineral coating includes two polymers or polymers and copolymers thereof in a ratio of about 1: 1. In some embodiments, the polymer in the mineral coating has a particle size of about 10 μm to about 500 μm or an average particle size of about 10 μm to about 500 μm.
[0120] In some embodiments, solvents can be used in the mineral coating. Suitable solvents that can be used in the mineral coating include, but are not limited to, acetic acid, alcohols, aliphatic ethers, aniline, chloroform, chlorinated hydrocarbons, aromatic hydrocarbons, aqueous alkali solutions, aqueous solutions of copper ethylenediamine, benzene, biphenyl, chlorinated aliphatic hydrocarbons, chlorinated hydrocarbons, chloroform, chlorophenol, chlorobenzene, cyclohexanone, chlorinated hydrocarbons, chloroauric acid, DCM, dimethylformamide (DMF), DMSO, dichlorobiphenyl, dioxane, dilute aqueous sodium hydroxide solution, 1,2-dichlorobenzene, dichloromethane, DCM, ethanol, ethyl acetate, ethylene carbonate, esters, formic acid, glycols, halogenated hydrocarbons, H FIP, higher aliphatic esters, higher aliphatic ketones, halogenated hydrocarbons, higher aliphatic esters, higher aliphatic ketones, ketones, higher ketones, hydrocarbons, isopropylamine, methyl ethyl ketone, morpholine, dichloromethane, methanol, methyl ethyl ketone, m-cresol, NMP, phenol, phenylenediamine, sulfuric acid, tetramethylurea, toluene, trifluoroacetic acid, THD, tetramethylurea, tetrahydrofuran (THF), trifluoroacetic acid, trichloroethanol, toluene, trichloroethane, trichloroacetaldehyde hydrate, perfluorokerosene, pyridine, phenyl ether, piperazine, pyridine, water or xylene, or a combination thereof.
[0121] In some embodiments, the solvent is selected from 2 or more of the following solvents: chloroform, acetic acid, formic acid, or a combination of formic acid and acetic acid. In some embodiments, the ratio of the two solvents is 4:1, 3:1, 2:1, or 1:1.
[0122] In some embodiments, the weight of the polymer to the volume of the solvent is about 1% w / v to about 10% w / v; or about 1% w / v, about 2% w / v, about 3% w / v, about 4% w / v, about 5% w / v, about 6% w / v, about 7% w / v, about 8% w / v, about 9% w / v, or about 10% w / v.
[0123] In some embodiments, the coating fluid comprises a calcium-containing mineral and further comprises NaCl, KCl, MgCl2, MgSO4, NaHCO3, CaCl2, KH2PO4, or a combination thereof to form a modified simulated body fluid.
[0124] In some embodiments, the coating solution comprises a calcium-containing mineral and further comprises: (i) a concentration of NaCl of about 100 mM to about 200 mM; (ii) a concentration of KCl of about 1 mM to about 8 mM; (iii) a concentration of MgCl2 of about 0.2 mM to about 5 mM; (iv) a concentration of MgSO4 of about 0.2 mM to about 5 mM; (v) a concentration of NaHCO3 of about 1 mM to about 100 mM; (vi) a concentration of CaCl2 of about 2 mM to about 20 mM; and (vii) a concentration of KH2PO4 of about 0.5 mM to about 10 mM. In some embodiments of the method, (i) the concentration of NaCl is about 141 mM; (ii) the concentration of KCl is about 4.0 mM; (iii) the concentration of MgCl2 is about 1.0 mM; (iv) the concentration of MgSO4 is about 0.5 mM; (v) the concentration of NaHCO3 is about 4.2 mM; (vi) the concentration of CaCl2 is about 5 mM; and (vii) the concentration of KH2PO4 is about 2.0 mM to form mSBF.
[0125] In some embodiments, the simulated body fluid includes a buffer comprising DPBS, Tris, Tris-HCl, Tris buffered saline, PBS, or a combination thereof. The concentration of the buffer may be in the range of about 3 mM to about 40 mM.
[0126] In some embodiments, the mineral coating comprises (i) about 9% to about 100% hydroxyapatite; (ii) about 90% to about 100% hydroxyapatite; or (iii) about 97% hydroxyapatite. In some embodiments, the mineral coating comprises (i) about 0% to about 30% octacalcium phosphate; (ii) about 0% to about 3% octacalcium phosphate; or (iii) about 3% octacalcium phosphate. In some embodiments, the mineral coating comprises a porosity between: (i) between about 2% to about 100%; or (ii) between about 20% to about 28%. In some embodiments, the mineral coating comprises (i) pores having a pore size of about 1 nm to about 3500 nm; or (ii) pores having a pore size of about 100 nm to about 350 nm.
[0127] In some embodiments, the bone particles to be coated include pore sizes ranging from (i) between about 200 μm and about 525 μm; (ii) from about 25 μm to about 65 μm; or (iii) greater than about 50 μm. In some embodiments, the bone particles include a large channel length greater than about 100 μm. In some embodiments, the mineral coating includes (i) about 0.1 Ca / P to about 18 Ca / P, or (ii) about 1.1 Ca / P to about 1.76 Ca / P (ratio of calcium to phosphate). In some embodiments, the mineral coating includes (i) about 1.67 Ca / P to about 1.76 Ca / P, (ii) about 1.1 Ca / P to about 1.3 Ca / P, or (iii) about 1.37 Ca / P to about 1.61 Ca / P.
[0128] In some embodiments, the mineral coating fluid includes a crystallinity concentration of: (i) about 9% to about 100%; (ii) about 90% to about 100%; or (iii) about 96.5%.
[0129] The bone particles can be coated with a mineral coating fluid by incubating the bone particles with the mineral coating fluid. For example, in some embodiments, the mineral coating fluid described herein can be prepared by incubating the bone particles in a modified simulated body fluid (mSBF) for four days or longer at a pH of about 6.8 to about 7.4 and a temperature of about 37°C. The mSBF can be renewed every day. In general, an increase in pH can be beneficial to the growth of hydroxyapatite, while a decrease in pH can be beneficial to the growth of octacalcium phosphate minerals.
[0130] In other embodiments, conditions favorable for hydroxyapatite formation may include a pH between about 5.0 and about 8.0 and a pH between about 10. -5 M and about 10 -8 The conditions that favor the formation of octacalcium phosphate may include a pH between about 6.0 and about 8.0 and a pH between about 10. -5 M and about 10 -7.5 The conditions favorable for the formation of dicalcium phosphate may include a pH between about 6.0 and about 8.0 and a pH between about 10. -4 M and about 10 -6 The calcium concentration between M is multiplied by the phosphate concentration.
[0131] In other embodiments, the pH of mSBF can be varied between about 5.0 and about 6.0 to promote the formation of hydroxyapatite. Similarly, the pH of mSBF can be varied between about 6.0 and about 6.5 to promote the formation of octacalcium phosphate and hydroxyapatite. Likewise, the pH of mSBF can be varied between about 6.5 and about 8.0 to promote the formation of dicalcium phosphate, octacalcium phosphate, and hydroxyapatite.
[0132] In some embodiments, the time period sufficient to form the coated bone particles is from about 1 day to about 4 days. In some embodiments, incubating the coating liquid with the bone particles to form the nanostructure-coated bone particles can be performed for a period of at least about 1 day; at least about 2 days; at least about 3 days; or at least about 4 days; or at least about 5 days; or at least about 6 days; or at least about 7 days.
[0133] In some embodiments, the coating fluid (e.g., mSBF) in contact with the bone particles is maintained, replaced, supplemented, removed, or has components added thereto, including, for example, polymers, solvents, buffers, or combinations thereof. In some embodiments, maintaining the concentration of the modified simulated body fluid includes replacing, supplementing, removing, or adding at least one of the following to the modified simulated body fluid: NaCl, KCl, MgCl2, MgSO4, NaHCO3, CaCl2, or KH2PO4KH, or combinations thereof. This can be accomplished using Figure 3A or Figure 3B equipment to complete.
[0134] In some embodiments, the coated bone particles are dried under conditions sufficient to form a continuous coating, which conditions include heating the coated bone particles to about 50°C to about 200°C, sufficient to soften, melt or solidify the coating on the bone particles.
[0135] In some embodiments, the method further comprises heating the coated bone particles for about 1 hour to about 6 hours, sufficient to soften, melt or cure the coating on the bone particles.
[0136] In many embodiments, the mineral coating covering the plurality of bone particles comprises a plate-like nanostructure comprising nanoparticles having a size range of about 100 nanometers to about 200 nanometers. In some embodiments, the nanoparticles may have a size range of about 10 nanometers to about 100 nanometers.
[0137] The shape and size of the coated bone particles create a high level of surface area, which increases uniform hydration when the fluid is applied to the bone particles. For example, due to the high level of surface area, the fluid will move rapidly into the bone particles by wicking. The bone particle shape can include a cylinder, a cube, a rod, or a tube (e.g., a solid or hollow tube); a semi-hemispherical hollow tube; one or more rectangles; one or more disks; electrospun fibers, or a combination thereof. The coated bone particles can also be freeze-dried.
[0138] In one embodiment, After the coating process is carried out on the particles, Figure 7 The scanning electron microscopy images in Figure 3 show that the lamellar nanomorphology of the coating on those coated particles is not destroyed. Particles are compared at a scale of 3 μm, which is also Figure 7 Obviously, Fig. 8A Compared to the conventional coating process illustrated in Figure 8B The bone particles coated with the nanoapatite surface coating exemplified in 2 / g to about 8.83m 2 / g of increased surface area, which means that the surface area increased by about 1106% to about 1804% (average 1300%). In this embodiment, the incubation time according to the coating method of the present application is only about 3 days, which is shorter than the conventional coating method. As described in Example 1, the coating method of the present application also increases the coated surface area of the bone particles by an average of 1300%.
[0139] In some embodiments, a coated porous ceramic particle having an increased surface area is provided, the porous ceramic particle comprising hydroxyapatite in an amount of about 8 to about 22 weight percent and beta-tricalcium phosphate in an amount of about 78 to about 92 weight percent. The porous ceramic particle has micropores having an average diameter of about 50 μm to about 800 μm, and each porous ceramic particle has an average particle size of about 0.25 mm to 2.0 mm, the porous ceramic particle having a mineral coating thereon, the mineral coating comprising nanostructures having an average size ranging from about 5 nanometers to about 500 nanometers, wherein the porous ceramic particle has a diameter of about 0.4 μm. 2 / g to about 9.5m 2 / g of BET surface area.
[0140] In some embodiments, coated bone particles are provided, which are prepared by the following method: providing a first mesh having a first set of openings to allow a coating liquid and bone particles of a selected size to pass through the first set of openings, and bone particles larger than the selected size are retained on the first mesh; adding bone particles to the first mesh; and contacting the bone particles with the coating liquid to allow bone particles larger than the first set of openings to be retained on the first mesh, and bone particles smaller than the first set of openings and the coating liquid to pass through the first set of openings, thereby coating the bone particles on at least the first mesh.
[0141] In some embodiments, a porous ceramic particle is provided, the porous ceramic particle being coated with a mineral coating, the mineral coating comprising nanostructures having an average size ranging from about 5 nanometers to about 500 nanometers, wherein the coated porous ceramic particle has a BET surface area of about 0.1 m 2 / g to about 9.5m 2 / g.
[0142] Mesh
[0143] In various embodiments, at least two meshes are used to coat the bone particles. The mesh and optional shell can be made of the same or different materials. In some embodiments, the mesh and optional shell can include materials that will not degrade or corrode in the coating solution. In some embodiments, the mesh and optional shell can include corrosion-resistant metal or plastic. In some embodiments, the mesh and optional shell can include materials that are the same or different from each other.
[0144] In some embodiments, the mesh and optional shell can comprise a polymer including an acrylic resin, an alginate, a caprolactone, a collagen, a chitosan, a hyaluronic acid, a hydrogel, a beta-hydroxybutyric acid, a nylon, a polyanhydride, a polycaprolactone (PCL), a poly(dimethylglycolic acid), a polydioxanone (PDO), a polyester, a polyethylene, a poly(ethylene glycol), a poly(glycolide) (PGA), a poly(glycolic acid), a polyhydroxybutyrate, a poly(2-hydroxyethyl methacrylate), a poly-lactide-co-glycolide (PLCG), a poly(D,L-lactide-co-glycolide) (PLG), a poly(lactide-co-glycolic acid) (PLGA), a polylactide (PLA), a polylactic acid (PLLA), a poly-lactide-co-glycolide (PLCG), a poly(methyl ethyl glycolic acid), a polymethyl methacrylate, a polyphosphazene, a polyphosphate, a polypropylene, a poly(propylene fumarate), a polyurethane (PU), or a silicone rubber, or a combination or copolymer thereof.
[0145] In some embodiments, the mesh can be made using nonwoven techniques such as needle punching, stitching, thermal or chemical bonding, hydroentanglement, felting, or point bonding, or using additive manufacturing methods (e.g., 3D printing). The mesh has a pore size large enough to allow small bone particles to pass through while retaining large bone particles.
[0146] The mesh is stackable. In some embodiments, the stackable mesh is formed into a U-shape so that each layer of the stackable mesh can be stacked on top of each other without a separate housing. The stackable meshes are spaced apart, wherein the distance between the bottom portion of the first mesh and the bottom portion of the second mesh ranges from about 0.5 inches, 0.75 inches, 1 inch, 1.25 inches, 1.5 inches, 1.75 inches, 2 inches, 2.25 inches to about 2.5 inches. In some embodiments, the length of the stackable mesh ranges from about 1 inch, 1.5 inches, 2 inches, 2.5 inches, 3 inches, 3.5 inches, 4 inches, 4.5 inches to about 5 inches. In some embodiments, the stackable mesh has a ratio of diameter to the distance between two stackable meshes. The ratio ranges from about 1:1, 1.5:1, 2:1, 2.5:1 to about 3:1. In some embodiments, the stackable mesh includes a depth extending from the topmost end of the top portion of the stackable mesh to the bottommost end of the bottom portion of the stackable mesh. Depths range from about 0.25 inches, 0.5 inches, 0.75 inches, 1 inch, 1.25 inches to about 2.5 inches.
[0147] In various embodiments, the mesh is made of braided wire. The wire of the mesh can have a predetermined thickness of about 0.01mm to about 2.0mm, about 0.05mm to about 1.0mm or about 0.1mm to about 0.5mm. The thickness of the wire can be uniform along the length of each wire, or the length variation across each wire. In some embodiments, some wires have a thickness greater than other wires. The size of the wire can be set to allow customizable openings or apertures between the wires. In some embodiments, the mesh is a fully customizable mesh, and its length and diameter can be adjusted according to the needs of the bone particle volume to be coated. For example, in some embodiments, the mesh is included in a length or width between about 0.1cm to about 24cm. In some embodiments, the mesh comprises a length or width of about 0.1 cm, 0.2 cm, 0.3 cm, 0.35 cm, 0.4 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, 0.9 cm, 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, 16 cm, 17 cm, 18 cm, 19 cm, 20 cm, 21 cm, 22 cm, 23 cm, or 24 cm.
[0148] The mesh can be a porous mesh so that the bone particles of coating liquid and some size can pass through the opening of the mesh.Porous mesh can have an opening or aperture of about 50 microns to about 1000 microns, to capture the bone particles of different sizes, and allow other bone particles to arrive at other meshes through the opening.In some embodiments, the opening of the mesh can be about 50 microns, 80 microns, 100 microns, 120 microns, 150 microns, 180 microns, 200 microns, 220 microns, 250 microns, 280 microns, 300 microns, 350 microns, 400 microns, 450 microns, 500 microns, 550 microns, 600 microns, 650 microns, 700 microns, 750 microns, 800 microns, 850 microns, 900 microns, 950 to about 1000 microns.Usually, the opening of the mesh changes according to the expected distribution of bone particles in each layer of stackable mesh. In some embodiments, when the bone particles include 100 microns to 300 microns, the first layer of stackable mesh (e.g., the first mesh) may have openings of 255 microns, the second layer of stackable mesh (e.g., the second mesh) may have openings of 212 microns, and the third layer of stackable mesh (e.g., the third mesh) may have openings of 160 microns.
[0149] When the bone particles have a similar distribution of different sizes, the bone particles are evenly distributed in each layer of the stackable mesh to maximize the contact area between the bone particles and the coating liquid. When the distribution is concentrated in a certain layer of the stackable mesh, the bone particles may gather together and reduce the contact surface area between the bone particles and the coating liquid. In some embodiments, the mesh can have various shapes, including a disc shape, a cylindrical shape, a square shape, or a rectangular shape.
[0150] How to use
[0151] In various embodiments, the bone particles of coating are used to form implantable bone implant or implantable composition, and this implantable bone implant or implantable composition can be implanted in bone defect.The bone implant with the bone particles of coating now has the surface area of increase, and this is conducive to hydration and bone remodeling of implant.In some embodiments, bone implant comprises one or more passages (it is recess), and this passage is not only used as surface marking but also increases surface area and the hydration characteristics of bone implant.Passage is the recess that can have macroscopic semi-cylindrical shape or other shapes (for example, disc shape, trapezoidal shape or square shape), and it can easily identify under visible light.
[0152] In various embodiments, the plurality of coated bone particles can be mixed with existing bone products such as bone strips, putties, and pastes. Such bone products can include, but are not limited to, those manufactured by Medtronic SofamorDanek, Inc. of Memphis, Tennessee. Bone strips; manufactured by Medtronic Sofamor Danek, Memphis, Tennessee Putty and / or Matrix EXT compression-resistant product from Medtronic Sofamor Danek, Memphis, Tenn.
[0153] In various embodiments, a method for treating a bone defect is provided. The method includes implanting a bone implant into the defect, the bone implant comprising porous ceramic particles, the porous ceramic particles comprising hydroxyapatite in an amount of about 8 wt % to about 22 wt % and beta-tricalcium phosphate in an amount of about 78 wt % to about 92 wt %, the porous ceramic particles having micropores with an average diameter of about 50 μm to about 800 μm, and each porous ceramic particle having an average particle size of about 0.1 mm to 2.0 mm, the porous ceramic particles having a mineral coating thereon, the mineral coating comprising nanostructures with an average size ranging from about 5 nanometers to about 500 nanometers, wherein the porous ceramic particles have a diameter of about 0.4 μm. 2 / g to about 9.5m 2 / g of BET surface area.
[0154] In some embodiments, the coated bone particles may have a particle size ranging from about 0.1 μm. 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.5m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.5m 2 / g, 4.0m 2 / g, 4.5m 2 / g, 5.0m 2 / g, 5.5m 2 / g, 6.0m 2 / g, 6.5m 2 / g, 7.0m 2 / g, 7.5m 2 / g, 8.0m 2 / g, 8.5m 2 / g, 9.0m 2 / g to about 9.5m 2In some embodiments, the porous ceramic particles before coating may have a BET surface area of about 0.1 m 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g to about 0.5m 2 / g of BET surface area.
[0155] In some embodiments, before, during or after implanting the bone implant into the bone defect, the bone implant comprising the mineral coating can be hydrated with a fluid comprising bone marrow aspirate, saline, sterile water, blood for injection, phosphate buffered saline, dextrose, Ringer's lactate solution or a combination thereof. The ratio of the fluid to the coated bone particles can be from about 0.5:1 to about 3:1. In some embodiments, the ratio of fluid to coated bone particles can be about 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 to about 3:1.
[0156] In some embodiments, the hydrated coated bone particles may have a flowable viscosity of about 50 Pascal-seconds (Pa-s), 100 Pa-s, 150 Pa-s, 200 Pa-s, 250 Pa-s to about 300 Pa-s, and reach a higher viscosity of about 500 Pa-s, 750 Pa-s, 1000 Pa-s, 1,500 Pa-s, 2,000 Pa-s, 2,500 Pa-s to about 3,000 Pa-s. In some embodiments, the hydrated bone particles may have a flowable viscosity of about 50 Pa-s to about 3,000 Pa-s and reach a higher viscosity of about 3,000 Pa-s to about 300,000 Pa-s.
[0157] The coated bone particles may have a certain density when hydrated. For example, when the coated bone particles are hydrated, the density may be from about 1.2 g / cc to about 2.0 g / cc or from about 1.4 g / cc to about 1.6 g / cc. In some embodiments, the hydrated bone particles may have a density of about 1.2 g / cc, 1.3 g / cc, 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, 1.8 g / cc, 1.9 g / cc to about 2.0 g / cc.
[0158] The coated bone particles once hydrated and placed into an implant may have an elastic modulus of about 2 MPa to about 12 MPa, e.g., about 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa to about 12 MPa.
[0159] Having now generally described the invention, the same may be more readily understood by reference to the following examples, which are provided by way of illustration and are not intended to limit the invention unless otherwise specified.
[0160] Example 1
[0161] Example 1 relates to a method for coating bone particles. Standard autografts are the gold standard for bone transplantation, but the supply and use of autografts are limited by donor site morbidity and suboptimal bone quality in some patients. Therefore, synthetic bone graft substitutes are increasingly used in clinical settings, although none of them are as effective as autografts. Therefore, we developed a nanoapatite coating, such as Figure 5 As shown, it grows on the implant surface and this results in implant performance characteristics approaching those of an autologous graft model. The coating is a bone mineral grown under physiological conditions by a biomimetic process. The coating has a plate-like nanostructure that is semi-crystalline and non-stoichiometric. The nanotopography is known to promote osteoblast adhesion and enhance osteoblast function by sensitively modulating protein interactions that lead to cell attachment, differentiation and proliferation.
[0162] However, coating a large number of micron-sized Particles are a challenge. This is because the interaction between particles during the normal coating process affects the quality of the nanotopography. An example of using micron-scale (90 μm to 600 μm) Improved methods for growing nanoapatite coatings on these challenging substrates. Figure 6 As shown, the coated bone particles according to the methods and apparatus provided herein have macropores and micropores.
[0163] Generally, the matrix (e.g., bone particles) is first cleaned in a caustic bath, rinsed, and then immersed in modified simulated body fluid (mSBF), which provides an environment rich in calcium and phosphate to promote crystallization. The mSBF is renewed daily for up to three days, then rinsed with water and finally dried.
[0164] For pilot scale, granulated bone particles ( ) were suspended in modified simulated body fluid (mSBF), such as Figure 1A, Figure 1B and Figure 3B As shown. The recirculating bath is used to maintain physiological temperature and ensure that a controlled rate of interaction between the mSBF and the particles occurs throughout the coating process. The stackable mesh allows the material density within the container to be increased while maintaining the flow of mSBF around the particles. Figure 4 As shown, once coating is complete, the mesh allows technicians to transfer the product directly to an oven for drying, thus preventing the individual particles from interacting with each other and disrupting the growth of the nanoapatite plates. Figure 7 A scanning electron micrograph comparing uncoated bone particles and coated bone particles is shown in . The specific surface area (SSA) increased from about 1106% to about 1840%, with an average of about 1300%, as shown in Table 1 below.
[0165] Table 1: Coated and uncoated Specific surface area of particles
[0166]
[0167] A pilot scale for improving the coating process has been successfully demonstrated. Scanning electron micrographs show that the plate-like nanomorphology of the coating is not damaged compared to the coating process carried out with the substrate at the bottom of the container. In addition, the specific surface area of the coated particles increased by an average of 1300% as measured by BET.
[0168] Although the present invention has been described with reference to preferred embodiments, workers skilled in the art will recognize that changes may be made in form and detail without departing from the spirit and scope of the invention.
Claims
1. A method for coating bone particles, the method comprising: providing a first mesh having a first set of openings to allow a coating fluid and bone particles of a selected size to pass through the first set of openings and bone particles larger than the selected size to be retained on the first mesh; adding bone particles to the first mesh; as well as The bone particles are contacted with the coating liquid so that bone particles larger than the first group of openings are allowed to remain on the first mesh and bone particles smaller than the first group of openings and the coating liquid pass through the first group of openings, thereby coating the bone particles on at least the first mesh.
2. The method according to claim 1, wherein: The method includes providing a second mesh having a second set of openings to allow the coating liquid and bone particles of a selected size to pass through the second set of openings, and bone particles larger than the selected size to be retained on the second mesh, the second set of openings of the second mesh being smaller in size than the first set of openings of the first mesh, the second mesh having a top portion, and the first mesh having a bottom portion, the bottom portion of the first mesh being stacked above the top portion of the second mesh to allow the coating liquid to pass through the second mesh, thereby coating the bone particles on at least the second mesh.
3. The method according to claim 2, wherein: The contacting includes adding the coating liquid to suspend the bone particles on the first mesh or the second mesh or both the first mesh and the second mesh.
4. The method according to claim 2, wherein: The contacting includes immersing the first mesh and the second mesh in the coating liquid so that the bone particles are suspended on the first mesh or the second mesh or on both the first mesh and the second mesh.
5. The method according to claim 4, wherein: Immersing the first mesh and the second mesh occurs in a container filled with the coating liquid.
6. The method according to claim 1, wherein: The coating liquid is added to the fill line of the forming bath, and the bone particles are positioned below the fill line.
7. The method according to claim 2, wherein: The second set of openings allows the coating fluid and bone particles smaller than the selected size to pass through the second set of openings to a housing or container configured to receive the mesh and contain any remaining coating fluid.
8. The method according to claim 7, wherein: The housing or the container has an outlet configured to be coupled to a pump to replenish the coating liquid.
9. The method according to claim 1, wherein: The coating liquid in contact with the bone particles forms a mineral coating on the bone particles, wherein the mineral coating comprises a calcium-containing mineral, wherein the calcium-containing mineral comprises at least one of apatite, hydroxyapatite, α-tricalcium phosphate, β-tricalcium phosphate, amorphous calcium phosphate, dicalcium phosphate, octacalcium phosphate, calcium carbonate, or carbonate-substituted calcium-deficient hydroxyapatite, inorganic bone, or a combination thereof, and the mineral coating has a thickness of about 50 nanometers to about 200 nanometers.
10. The method according to claim 1, wherein: Contacting the bone particles with the liquid coating forms plate-like nanostructures on the bone particles, the plate-like nanostructures comprising nanostructures having a size ranging from about 100 nanometers to about 200 nanometers.
11. The method according to claim 1, wherein: The coating liquid contacts the bone particles to form a surface coating on the bone particles.
12. The method of claim 2, further comprising drying the bone particles retained on the first mesh, the second mesh, or both the first mesh and the second mesh in an oven.
13. The method according to claim 2, wherein: The method further includes stacking at least a third mesh, a fourth mesh, a fifth mesh, or a sixth mesh below a bottom of the second mesh.
14. The method according to claim 1, wherein: The method also includes providing an additional mesh having a set of openings having the same size as the openings of the first mesh, and contacting the additional mesh with the coating fluid and bone particles.
15. The method according to claim 1, wherein: The first mesh is only a single mesh.
16. The method according to claim 1, wherein: The method also includes providing an additional mesh having a set of openings to allow the coating liquid to pass through the set of openings, the additional mesh having a bottom portion, the bottom portion of the additional mesh stacked over the top portion of the first mesh.
17. An apparatus for coating bone particles, the apparatus comprising: a first mesh having a first set of openings, the first set of openings being configured to allow a coating fluid and bone particles of a selected size to pass through the first set of openings, and bone particles larger than the selected size to be retained on the first mesh; and A housing or container at least partially encloses the first mesh, the housing or container having an outlet configured to be fluidly coupled to a pump configured to provide the coating liquid to at least the first mesh to coat the bone particles.
18. The apparatus according to claim 17, wherein: The device includes a second mesh having a second set of openings, the second set of openings being configured to allow the coating liquid and bone particles of a selected size to pass through the second set of openings, and bone particles larger than the selected size to be retained on the second mesh, the second set of openings of the second mesh being smaller in size than the first set of openings of the first mesh, the second mesh having a top portion, and the first mesh having a bottom portion, the bottom portion of the first mesh being configured to be stacked above the top portion of the second mesh.
19. A porous ceramic particle comprising hydroxyapatite in an amount of about 8 wt % to about 22 wt % and beta-tricalcium phosphate in an amount of about 78 wt % to about 92 wt %, the porous ceramic particle having micropores with an average diameter of about 50 μm to about 800 μm, and each porous ceramic particle having an average particle size of about 0.1 mm to 2.0 mm, the porous ceramic particle having a mineral coating thereon, the mineral coating comprising nanostructures with an average size ranging from about 5 nanometers to about 500 nanometers, wherein the coated porous ceramic particle has a diameter of about 0.1 mm to about 2.0 mm. 2 / g to about 9.5m 2 / g of BET surface area.
20. The porous ceramic particle according to claim 19, wherein The mineral coating comprises a calcium-containing mineral, which is at least one of apatite, hydroxyapatite, α-tricalcium phosphate, β-tricalcium phosphate, amorphous calcium phosphate, dicalcium phosphate, octacalcium phosphate, calcium carbonate or carbonate-substituted calcium-deficient hydroxyapatite, inorganic bone, or a combination thereof, and the coating has a thickness of about 50 nanometers to about 200 nanometers.
Citation Information
Patent Citations
Hydratable and flowable implantable compositions and methods of making and using them
US11433159B2
Mineral-coated microspheres
US11607391B2
Mineral-coated microspheres
US20140161886A1
Coating scaffolds
US20160271296A1
Hydratable and flowable implantable compositions and methods of making and using them
US20210023258A1